Imputing age at death for the deceased using household relationships - Chinanayi, Farai S (Centre for Actuarial Research (CARE), 2014)
Immeasurable effort has been dedicated to estimating mortality using direct and indirect demographic techniques. However, literature available on methods applied to replacing missing values for non-responses in surveys or censuses so that these methods are implemented using sound data is sparse. The National Income and Dynamics Study (NIDS) household dataset includes the relationship of the deceased to the head of household variable. The relationship of the deceased to the head of household and the age of the head of household are incorporated into the Multiple Imputation (MI) technique proposed by Rubin (1987) to impute the missing ages at death for the deceased.